2015
DOI: 10.1111/azo.12124
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine phosphorylation as evidence of epididymal cauda participation in the sperm maturation process of Corynorhinus mexicanus bat

Abstract: The bat Corynorhinus mexicanus provides an interesting experimental model for the study of epididymal sperm maturation because after spermatogenesis and the regression of the testes, this bat stores sperm in the epididymal cauda for several months. Earlier research conducted by our group suggested that sperm maturation in this species must be completed in the caudal region of the epididymis. One of the major signal transduction events during sperm maturation is the tyrosine phosphorylation of sperm proteins. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(45 citation statements)
references
References 31 publications
2
28
1
14
Order By: Relevance
“…All captures were done before the animals left their roost (12:00 -16:00 hours) using an expanded hand-net (Bioquip Tropic net). The adult category and the reproductive condition of the individuals included in this study were stablished in accordance with reports by León-Galván et al (2005), Cervantes et al (2008), and Rodríguez-Tobón et al (2016, taking into account the following variables: body weight, recorded using an Ohaus® (Ohaus Corporation, Parsippany, NJ, USA) portable electronic balance (±0.01 g); forearm length, measured with a vernier caliper (±0.1 mm); and by the external aspects of the sexual organs. A total of 26 bats were included in the study.…”
Section: Chemicals and Animalsmentioning
confidence: 81%
See 2 more Smart Citations
“…All captures were done before the animals left their roost (12:00 -16:00 hours) using an expanded hand-net (Bioquip Tropic net). The adult category and the reproductive condition of the individuals included in this study were stablished in accordance with reports by León-Galván et al (2005), Cervantes et al (2008), and Rodríguez-Tobón et al (2016, taking into account the following variables: body weight, recorded using an Ohaus® (Ohaus Corporation, Parsippany, NJ, USA) portable electronic balance (±0.01 g); forearm length, measured with a vernier caliper (±0.1 mm); and by the external aspects of the sexual organs. A total of 26 bats were included in the study.…”
Section: Chemicals and Animalsmentioning
confidence: 81%
“…To extract of the sperm, every couple of epididymal regions were placed in 500 µL of Ringer at 37.8°C, finely minced and kept under agitation for 5 min to allow the spermatozoa to break free from the epididymal tubules. Subsequently, the minced material was collected with a Pasteur pipette and filtered by passage through a 20-µm-diameter-weft Lycra mesh (98% nylon/polyamide, 2% Lycra/elastane), and the fluid was collected in a 2 mL Eppendorf tube (Arenas-Ríos et al, 2005;Rodríguez-Tobón et al, 2016). The sperm suspension was washed by centrifugation at 500 g for 5 min; then, the supernatant was removed, and the cell pellet was re-suspended in 1 mL of Ringer.…”
Section: Chemicals and Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been reported that, unlike other mammalian species in C. mexicanus, the epididymal sperm maturation ends in caudal region [24,35], showing that it is the month of October, the most important, as it was in that month, in which, an important tyrosine phosphorylation of protein in sperm increase, was detected [35], and it is from this date, that sperm were found with the ability of capacitation and to experience acrosome reaction [24,35].…”
Section: Discussionmentioning
confidence: 95%
“…However, studies of tyrosine phosphorylation have been conducted mainly in species in which the sperm maturation process is seen to end before the spermatozoa enter the epididymal cauda. In the case of C. mexicanus, it has been determined that tyrosine phosphorylation increases in sperm obtained from the cauda [31], clearly indicating that the sperm maturation process continues there. And this finding, in turn, may be related to the time that the sperm are stored in the cauda.…”
Section: Tyrosine Phosphorylationmentioning
confidence: 99%